The Impact of Strategic Leadership Practices on Improving Organizational Performance: A Case Study of Al Sharara Al Zahabiya Oil Services Company – Libya (Al-Farooq Journal of Sciences, 2026)
This study examined the impact of strategic leadership practices on organizational performance at Al-Sharara Golden Oil Services Company in Libya. A descriptive-analytical approach was adopted, and data were collected through a questionnaire administered to a sample of 120 employees. The results revealed a strong and statistically significant positive relationship between strategic leadership practices and organizational performance, with an overall correlation coefficient of (r = 0.81). The coefficient of determination reached (R² = 0.66), indicating that strategic leadership practices explained 66% of the variance in organizational performance. Multiple regression results showed that developing organizational resources and capabilities had the strongest effect, followed by strategic vision and direction, and then change management and organizational culture. The study concludes that strengthening strategic leadership practices can enhance operational efficiency, performance quality, and achievement of organizational objectives.
Keywords: Strategic Leadership, Organizational Performance, Organizational Capabilities, Change Management